Development Of Haccp Plan For Flour Production Line - E. Semercioglu; A. Kasımakunova; R. Adil Akai Tegin (MANAS: Journal of Engineering)
In this study, it is aimed to determine the critical control points of a flour production line in a millot Kyrgyzstan. Hazard analysis of the production line was done and 5 different critical control points have been identified and corresponding process steps are classified as follows: Reseiving of wheat, storage of wheat, removal of foreign materials by metal magnite, storage of ready-made product without packaging, storage of ready-made product. The safety of control points outside the critical control points is ensured by prerequisite programs. The HACCP Plan has been established for the process steps that are considered as critical control point.